Saberes e fazeres docentes na educação infantil : tempos formativos e a constituição da docência - Silveira, Carla Tatiana Moreira do Amaral (2021)
This study aims to analyze and understand which formative experiences constitute the knowledge and practices of teaching in Early Childhood Education. It is from a qualitative perspective, using a semi-structured interview (LÜDKE; ANDRÉ, 1986) and the focus group (BAUER; GASKELL, 2002) as a methodological strategy for data collection. The study subjects were teachers working with Children´s Education, whose scenario was a Public Children Education School, located in Serra Gaúcha. For the analysis of the material, the research was based on Content Analysis, by Bardin (2009). From this process, five categories were analyzed and evidenced the formative times experienced by teachers in the constitution of their knowledge and doing. Since these times revealed, among other aspects, the importance of modifying the curricular structure of initial training courses, so that new theoretical bases can be invested, highlighting the peculiarities of teaching in/for Children´s Education. In continuing education, collective practices have manifested themselves as a possibility for the expansion of new constitutive paths in teaching. The participants of this study also demonstrated understand how much BNCC and specific approaches to childhood have opportunities for important teacher reflections, including the opening to new pedagogical actions in Children´s Education. The principles of care, welcoming, ethics, empathy, respect, care, and affection also stood out as fundamental to pedagogical practice in Children´s Education. The pandemic manifested itself as a time of expansion of knowledge and teaching and also as a time of sharing in the search for an integral education for young children. The narratives also indicated a possible openness and even a need for reflection and resignification of pedagogical action in Children´s Education. Based on all the data presented and explored in this study, the thesis signals the existence of a new formative time, that is, a time to (re) learn to be a teacher from listening to the manifestations of children in the daily life of Children´s Education.